2019
DOI: 10.4102/curationis.v42i1.1912
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to the Integrated School Health Policy: Intersectoral and multisectoral collaboration

Abstract: Background: Implementation of the Integrated School Health Policy (ISHP) requires strong intersectoral collaboration on the part of key role players such as the Department of Health, Department of Basic Education and Department of Social Development. These departments and educational structures such as school governing bodies, teacher unions and learner organisations, academic institutions, civil society and development partner organisations are also expected to contribute to the development of sustainable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…Respondents were of the view that preschool vision screening has not been incorporated into the schools' curriculum, and that no written policy exists for Ghanaian preschoolers. Respondents' views were contrary to the government-supported vision screening programmes and policies for children of school-going age in other countries [9,10,12,13]. An important and novel finding in this current study was the observation that children are not screened at the time of preschool enrolment.…”
Section: Plos Onecontrasting
confidence: 69%
See 1 more Smart Citation
“…Respondents were of the view that preschool vision screening has not been incorporated into the schools' curriculum, and that no written policy exists for Ghanaian preschoolers. Respondents' views were contrary to the government-supported vision screening programmes and policies for children of school-going age in other countries [9,10,12,13]. An important and novel finding in this current study was the observation that children are not screened at the time of preschool enrolment.…”
Section: Plos Onecontrasting
confidence: 69%
“…The introduction of a joint policy statement on vision screening by Practice and Medicine [7] has provided basic recommendations for vision screening in children. Preschool vision screening programmes and policies have been implemented in many countries, including the United States [8], Canada [9], United Kingdom [10], Sweden [11], Australia [12], and South Africa [13]. These vision screenings identify the causes of ocular morbidity in children and offer the best treatment/ management practice, as well as ensuring the consistent availability of vision screening to school-aged children.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, Lenkokile, Hlongwane and Clapper (2016:2) add that not all the schools are disseminating and implementing the school health policy effectively. This is in line with the findings of Rasesemola, Matshoge and Ramukumba ( 2019 :2) who indicated that the implementation of school health policies has been a challenge in sub-Saharan countries such as Nigeria, South Africa, Botswana and Ghana. The absence of policies and/or the lack of proper dissemination and implementation has negative effects on school children (Hourani & Litz 2018 :38).…”
Section: Introductionsupporting
confidence: 91%
“…The implementation of similar policies [17] that rely on collaborations between the DoH and DoE has proven somewhat challenging. [18][19][20] Therefore, the success of…”
Section: Discussionmentioning
confidence: 99%